Tailored photocatalyst for azo Solochrome Dark Blue (SDB) dye removal: Characterization and performance of α-Fe2O3 on neem leaves-derived activated carbon - Neeta Gupta; Ashok Raj Patel; Ashish Tiwari (Next Materials)
This study investigates the development of a tailored adsorbent for the efficient removal of Solochrome Dark Blue (SDB), a hazardous azo dye. The adsorbent is synthesized by loading α-Fe2O3 nanoparticles (NPs) onto activated carbon derived from Neem leaves. The research encompasses the synthesis process, characterization of the α-Fe2O3@C nanocomposite, and evaluation of its adsorption performance towards SDB dye. Characterization techniques such as Raman spectroscopy, X-ray diffraction (XRD), FT-IR spectroscopy, scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS) analysis were employed to investigate the nanocomposite's morphology, structure, and textural properties. The of a Raman spectrum, with a graphitization degree of 0.91 and peaks at 1350 cm-1 and 1595 cm-1, confirmed the formation disordered graphite-like structure. The XRD analysis confirmed the formation of the hematite phase (α-Fe2O3). The strong band around 1630 cm−1 is associated with CC stretching vibrations, and the intense absorption band at 638 cm−1 in the FT-IR spectrum, attributed to the symmetric stretching mode of Fe-O, confirmed the formation of α-Fe2O3@C. The adsorption performance was assessed by examining the influence of various parameters, including initial SDB dye concentration, light effect, contact time, solution pH, and H2O2 concentration effect. The results indicated that alkaline conditions favored degradation, with the highest degradation rate (99.94 %) achieved at pH 6. The complete degradation in 80 min of SDB was observed. Moreover, the nanocomposite exhibited outstanding reusability, effectively retaining its catalytic performance over eight consecutive cycles following straightforward filtration and recovery. This research aims to develop sustainable and efficient strategies for removing azo SDB dyes from wastewater.